Design of a Wireless Control System Using a Bluetooth Module for an Oil Purifier Robot - Setya Permana Sutisna; Roy Waluyo; Addiena Syahvina Nasution; Muslim Ilyas (Universitas Ibn Khaldun Bogor, 2023)
The sea is one of the sources of wealth in Indonesia. Damage to and on the sea greatly impacts marine ecosystems and the livelihoods of people on the coast. Oil spills are the main source of marine pollution. Several ways of handling oil spills are carried out utilizing mechanical removal, using sorbents, and using dispersants. This countermeasure is carried out in offshore sea areas so that large ships and human resources are needed are many and qualified technologies needed that can help handle oil spills can be done remotely by designing a wireless system that can control an unmanned waste oil cleaning robot. This study aims to get the results of Bluetooth module as a wireless control system for waste oil cleaning robots and to implement Bluetooth module for this robot control system. The design of this robot control system utilizes the HC06 Bluetooth module as a connection to connect to the smartphone and uses the Arduino Uno R3 block to enter algorithm programming to be able to drive a waste oil cleaning robot. Bluetooth module testing is carried out with treatment with and without obstacles with a range of 1-15 m. Tests were also carried out to move the robot to go forward, backward, and turn right, and left. The control of the waste oil cleaning robot can be properly connected at all ranges with unhindered treatment at all ranges. While the treatment with obstacles can only be connected up to a distance of 9 m. The performance of the cleaning robot to move forward, backward, turning right, and left with a 100% success rate. Based on the test data, it can be concluded that the Bluetooth module HC06 and Arduino Uno R3 can be applied to control robots cleaning waste oil.